Effect of community-based food supplementation on improving growth of underweight children under five years of age in West Nusa Tenggara - Aman Bhakti Pulungan; Dini A. Mirasanti (Indonesian Pediatric Society, 2017)
Background The prevalence of underweight children in West Nusa Tenggara is as high as 30%. This region had the third largest number of stunted children in the country. The local government has attempted to tackle this problem by providing supplementary food to underweight children.Objective To assess the success of the community-based food supplementation program onimproving children’s growth in West Nusa Tenggara.Methods We conducted a prospective cohort study for 10 months in Paruga District Primary Health Care Unit, Bima, West Nusa Tenggara, in year 2012. Children were given supplementary food according to the Ministry of Health’s guidelines, consisting of formula milk, high calorie biscuits, and a 60-day supply of eggs, estimated to be sufficient to normalize their weights, for their age and sex. A child’s weight and height were measured every 3 months and the results plotted on WHO growth charts for weight-for-age, height-for-age, and weight-for-height (nutritional status). Z-score <-3 SD was classified as severely underweight, severely stunted, or severely wasted, respectively; Z-score between -2 and -3 SD was classified as underweight, stunted, or wasted, respectively; and Z–score >-2 SD was classified as normal for all three categories.Results Twenty-five children under five years of age participated in this study. Subjects’ median age was 29 months. None of the subjects had normal weight-for-age Z-score at the beginning of the study. Eighty-four percent (21/25) of the subjects were severely underweight. Only 8% (2/25) of the subjects had normal height-for-age Z-score and 88% (22/25) of them were severely stunted. However, 80% (20/25) of subjects had normal nutritional status (weight-for-height). Changes in weight-for-age Z-score varied throughout the study. The highest median score was in the tenth month of follow up (-3.82). The highest median height-for-age score and weight-for-height score were also in the last month of follow up. At the end of the study, only one subject had normal weight-for-age score (4%) and none of the subjects had normal height-for-age scores. Conclusion The 10-month supplementary food program for under-five children in the Paruga District is not successful in improving body weight and height.